Environmental impact assessment of agricultural pesticides - Schaaf, Alejandro Alberto (Observatorio Medioambiental, 2015)
The use of agrochemicals in Argentina has strengthened along with agricultural expansion. The aim of this paper is to draw up a methodology to calculate the environmental impact that pesticides cause in the environment considering the following factors: “ecotoxicology”: toxicological category, toxicity to bees, birds and fish; “human toxicity”: carcinogenicity, neurotoxicity, endocrine disruption, genotoxicity and irritative capacity; “environmental behavior”: persistence in water / sediment, soil persistence and bioconcentration. These factors were then categorized as Low, Medium, High or Very High, according to their toxicity level. Results indicate that the most toxic pesticides are among the group of insecticides. Most of the pesticides used are middle toxicity (43.75%), followed by high and low toxicity (21,88%) and finally the very high toxicity (12.5%). The proposed methodology could be used either as a monitoring tool, for management or environmental education.
Keywords: Chemicals; toxicity; environmental monitoring.